Bridging global goals and local contexts: Advancing equity and human rights in university classrooms - Sheridan , Robert; Tanaka, Kathryn (Journal of International Students, 2026)
This paper examines ways to integrate social justice and human rights education into international university courses taught through English as a foreign language (EFL) and content and language integrated learning (CLIL) in Japanese universities. Grounded in the Sustainable Development Goals (SDGs), this study connects these goals to human rights issues to create culturally relevant, student-centered lessons that develop intercultural and linguistic competence while raising awareness of diversity, equity, and social justice. Drawing on classroom observations, material trials, and surveys, this paper proposes a framework for designing curricula that link global social justice themes, such as gender equality and climate justice, with local contexts and student experiences.